Computed tomographic cervical myelography in horses: Technique and findings in 51 clinical cases. (24th July 2020) - Gough, Sarah L.; Anderson, Jonathan D. C.; Dixon, Jonathon J
Abstract: Background: Three‐dimensional computed tomographic (CT) evaluation of the cervical vertebral column enables more accurate identification of osseous and soft tissue lesions than traditional latero‐lateral radiography. However, examination of the complete cervical vertebral column has been limited by horse size, preventing evaluation of the caudal cervical vertebrae. Objectives: To describe a technique to enable CT myelography of the complete cervical spine and describe the findings in 51 horses. Animals: Records of 51 horses presented for evaluation of cervical vertebral lesions. Methods: A retrospective review of clinical records from all horses presented for CT myelography to further investigate possible cervical vertebral lesions was performed. A description of a novel approach to CT myelography in horses and retrospective review of the findings in clinical cases has been included. Results: Degenerative joint disease was identified at 1 or more dorsal articular process joint in 50/51 horses, of which 44/51 had a site of grade 2 or greater. Spinal cord compression was observed on CT myelography in 31/51 horses, whereas attenuation of the dorsal contrast column was identified radiographically in 11/50 horses. Thirty‐three horses showed narrowing or obliteration of the intervertebral foramina at 1 or more site and osteochondral fragments were seen in 11/51 horses. Conclusions and Clinical Importance: Computed tomography myelography is relatively safe and an easily performed technique with the correct equipment, enabling evaluation of the cervical vertebral structures of horses in all planes and volumetrically. It is possible that lesion extent might be underestimated with this diagnostic modality, hence interpretation should be complimented with flexed and extended views radiographically.